Linear polyethylenimine as (multi) functional initiator for organocatalytic l-lactide polymerization. Issue 4 (27th November 2014) - Coulembier, Olivier; Moins, Sébastien; Maji, Samarendra; Zhang, Zhiyue; De Geest, Bruno G.; Dubois, Philippe; Hoogenboom, Richard
Abstract : The preparation of polyethylenimine (PEI)–polylactide (PLA) copolymer structures is promising as these materials may find use in gene and/or drug delivery applications. Abstract : The preparation of polyethylenimine (PEI)–polylactide (PLA) copolymer structures is promising as these materials may find use in gene and/or drug delivery applications. In the current work we have explored the utilization of linear polyethylenimine (L-PEI) as multifunctional initiator for the organocatalytic ring-opening polymerization of lactide. Evaluation of the effect of the amount of catalyst revealed that with high catalyst loadings mixtures of unmodified L-PEI and PEI–PLA were obtained while low catalyst loadings leads to efficient preparation of PEI–PLA graft copolymers. This difference is described to the enhanced polymerization time with lower catalyst loading enabling efficient initiation from up to every second ethylenimine unit. The resulting PEI–PLA were subsequently formulated into nanoparticles of ∼400 nm by nanoprecipitation, which could be efficiently labeled with rhodamine octadecylester as model hydrophobic drug. These nanoparticles were efficiently taken up by DC2.4 cells as demonstrated by flow cytometry and fluorescence microscopy demonstrating their potential for gene and/or drug delivery applications.